The Relationship Between Hepatopulmonary Syndrome and Altitude - Morgan A Valley; James F Trotter; Deborah Thomas; Adit A Ginde; Steven R Lowenstein; Benjamin Honigman (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: In a previous small retrospective study, the authors reported that hepatopulmonary syndrome was less common among liver transplant candidates at high-altitude centres compared with low-altitude centres.